EDUCATION INTELLIGENCE SOFTWARE AS A TOOL OF INCREASING THE EFFECTIVENESS OF CREATIVE LEARNING - Hryshachov, Victor; Zamyatin, Denys; Kebkalo, Olexy; Mykhailiuk, Anton; Ohnivchuk, Lesya; Tarasenko, Volodymyr (International Journal of Computing, 2011)
A mathematical model of learning in the way of self information-educational activity of a student is developed in his article. A method for constructing and optimizing of individual educational trajectories is proposed. The impact of the use of specialized information and analytical systems on quality scores of the learning process is analyzed. This paper introduces the concept of Education Intelligence systems and shows that their use in an education process is a powerful tool of the intensification of the training activities.